Viability of Rare Fish Species in the Water Biotopes of the Khorezm Oasis and the Ecological Factors Determining Them - Babadjanova Sayyora Xushnutovna (American Journal of Botany and Bioengineering, 2026)
In this article, based on scientific sources, the viability of rare and valuable fish species in the main aquatic biotopes of the Khorezm oasis (stepped environment, its rate, success of reproduction) and the quality of their determining ecological analysis, water, chemical indicators, water temperature, mineralization, water content, the state of the chemical base, and the influence of anthropogenic fluid (reclamation, water, pollution) on fish survival were highlighted. With the help of supporting tools, it helps to maintain safety measures.